2020
DOI: 10.1590/fst.31618
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity and hepatoprotective effects in obese rats fed diets supplemented with fruit purees

Abstract: Four puree formulations, guava-strawberry (GSP), guava-blackberry (GBP), guava-soursop (GSSP) and guava-passion fruit (GPP) purees, were donated by Purés y Derivados de Nayarit (PDN), Camichin de Jauja, Nayarit, Mexico. The elaboration, characteristics, nutritional composition and content of bioactive compounds of the purees were described in a previous publication (Pérez-Beltrán et al., 2017). 2.2 Experimental diets Six diets were used. A commercial pedestrian maintenance diet for experimentation (Nutri cubo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Fruit puree have a large content of vitamin D. It is found that obese rats who eat a low-fat diet supplemented with fruit puree can reduce the weight of obese rats, control blood lipid metabolism, reduce the levels of total cholesterol and triacylglycerol, reduce the expression of inflammatory markers, reduce liver injury and improve the morphology of liver, eating fruit puree may help to control and improve obesity complications caused by lipoprotein changes (Morales-Avila et al, 2020). Vegetables and fruits are also important sources of vitamin D and contain anthocyanins.…”
Section: Vitamin D and Foodmentioning
confidence: 99%
“…Fruit puree have a large content of vitamin D. It is found that obese rats who eat a low-fat diet supplemented with fruit puree can reduce the weight of obese rats, control blood lipid metabolism, reduce the levels of total cholesterol and triacylglycerol, reduce the expression of inflammatory markers, reduce liver injury and improve the morphology of liver, eating fruit puree may help to control and improve obesity complications caused by lipoprotein changes (Morales-Avila et al, 2020). Vegetables and fruits are also important sources of vitamin D and contain anthocyanins.…”
Section: Vitamin D and Foodmentioning
confidence: 99%
“…The strawberry (Fragaria ananassa) is a fruit comprised of components with important physiological activity: vitamin C, tannins, flavonoids, anthocyanins, catechin, quercetin and kaempferol, organic acids (i.e., citric, malic, oxalic, salicylic, and ellagic), and minerals (i.e., K, P, Ca, Na, and Fe) (Kallio et al, 2000;Mosquera, 2010;Ribeiro et al, 2018). As such, it is considered a functional food with multiple health benefits demonstrated by its antioxidant, anti-inflammatory, anti-hypertensive, and anti-proliferative properties (Gasperotti et al, 2015;Bastos et al, 2019) and hepatoprotector activity (Morales-Ávila et al, 2020). Additionally, the strawberry is characterized by its bright red color, a unique flavor defined by the balance of sugar and acidity, and a white or red pulp according to the variety (Perin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional chemotherapy drugs, TCMs are less toxic, causing fewer side effects, and are relatively inexpensive. (Mostafa et al, 2021;Wang & Jin, 2021;Morales-Ávila et al, 2020) TCMs have been combined with various conventional clinical therapies to treat HCC and may enhance tumor sensitivity to radiotherapy and chemotherapy, reduce toxicity and side effects, and improve the quality of life and survival rate of patients (Ling et al, 2018).…”
Section: Introductionmentioning
confidence: 99%